DEBT OR EQUITY? Pespective Cooperation on Shipping Sector - Suparta, I Made (Program Doktor Ilmu Ekonomi, 2019)
This study discusses corporate finance in order to enlarge the company's capacity. There are two ways to finance this, namely by issuing debt securities and by selling someshares to other parties or to the general public. Data is taken from 24 shipping companiesthat provide transportation services listed on the Indonesia Stock Exchange through RTIBusiness in the form of liabilities, equity, DER, ROA and ROE. To analyze the data used descriptive analysis and correlation analysis techniques. Although the correlation between DER and ROA gives positive results, it does not provide information on whichstocks are suitable for investors to choose in investing. When viewed from the value ofROE, investors can choose companies that have ROE above 15% and a positive DERvalue. In the research there are two shipping companies that have ROE above 15%,namely HITS and TCPI. In choosing a source of corporate funding, management must becareful. Debt that is too large compared to the ability to pay together with the interest isvery burdensome for the company. This can reduce the value of assets and inhibit theincrease in company equity. If a company has very stable cash flow, it can use more debt than companies inrisky industries or very small companies that are just starting to operate. New businesseswith high uncertainties may have difficulty obtaining debt financing and better financetheir operations mostly through equity.Keyword: debt, equity, DER, ROA, ROE.